Aspectos de uma polícia profissional e a Polícia Federal Brasileira: o caso dos escrivães, papiloscopistas e agente – EPA – de polícia federal lotados em Foz do Iguaçu-PR - Leite, William Cordeiro (2015)
The objective of this research was to identify the aspects of a professional police force found in the specialized literature on the subject and to compare them to the Brazilian Federal Police, using bibliographical, documentary and field research. To this end, we researched the concepts of police professionalization in the literature and determined that its definition is controversial and complex and that the reforms that took place in western police forces, primarily in the USA and England, from the end of the 19th century to the middle of the 20th century, created a bureaucratic police model, with a militarized structure and emphasis on enforcing the law. This model influenced the professional model of Brazilian police forces, and more specifically, the Brazilian Federal Police. Ten primary aspects of a professional police force were identified. These were divided into 18 items, and documentary research was performed to determine how these aspects were present in the Brazilian Federal Police. Some hypotheses/assumptions were formulated concerning the problems that were discovered. Subsequently, quantitative research was performed, through a structured questionnaire, with 25 questions, to a sample of federal police officers with the positions of Agent, Clerk and Forensic Print Analyst of the Federal Police crowded into the Federal Police Station in Foz do Iguaçu, in the state of Paraná, about the aspects found in the documentary research. In the research, we were able to verify that the items with the greatest problems were those related to the police career (class promotion, job duties and performance evaluations), internal control (internal inspection structure and enforcement of the penalty), compensation, courses for class advancement in the career and the democratic relationship among police public servants. Concerning the items with the best assessments, those which stand out were those related to the professional training of the police officer, police ethics and the democratic relationship between the federal police officer and the citizen